IMPLEMENTASI MEDIA PLATFORM EDUKASI GEOSPASIAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR SPASIAL SISWA FASE F PADA MATERI KEANEKARAGAMAN HAYATI DI SMAN 15 PADANG - Maulana Ibrahim, Reyhan; Bayu Wijayanto; Yurni Suasti; Ahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of using geospatial educational technology media on improving the spatial thinking skills of students at SMAN 15 Padang. The research method used in this study was a quasi-experimental method with a nonequivalent control group design. The sample of this study was class XI F10 as the experimental class and class XI F4 as the control class, which were randomly selected. Spatial thinking data were collected through tests and analyzed using t-tests. The results found that geospatial educational technology media influenced the spatial thinking skills of class XI F10 students at SMAN 15 Padang, with an average posttest score of 84.0 for the experimental class and 62.4 for the control class.